Skeletal muscle tissue changes with hypoxia - Hoppeler, H.; Mueller, M.; Vogt, M. (High altitute: Human adaptation to hypoxia, 2014)
This review summarizes results of research into the effect on skeletal muscle tissue of prolonged exposure to high (3,000-5,500 m) and extreme altitude (>5,500 m). There is consensual evidence that continued sojourn at these altitudes has a number of negative consequences to muscle tissue. There is a loss of muscle mass related to a decrease of individual muscle fiber cross-sectional area. There is also a relative and absolute decrease in muscle oxidative capacity which manifests itself as a decrease in mitochondrial volume as well as a decrease in oxidative enzyme activities. The capillary to fiber ratio is maintained in hypoxia with the consequence that, without capillary neoformation, the oxygen supply of remaining mitochondria is improved. There is further a massive increase in lipofuscin, a lipid peroxidation product. Hypoxia activates defensive cellular mechanisms, among them the well-characterized response to the hypoxic master gene HIF (hypoxia-inducible factor). Reactive oxygen species (ROS) abound under hypoxic conditions and are further responsible for the orchestration of the hypoxia response. The permanent hypoxic stress of living at high altitude has led to a number of disparate but effective phylogenetic adaptations in native high-altitude populations, Tibetans and Quechua. When hypoxia is used as an adjunct limited to exercise training sessions, skeletal muscle tissue responds with a specific molecular signature. The functional consequences of which may offer benefits for competition at altitude.